Pemanfaatan Pekarangan sebagai Upaya Peningkatan Ketahanan Pangan - Aliefman Hakim; Ellend Putri Kurnia; Nurul Lasmini; Ade Nusa Putra Dinata; Idmayanti Idmayanti; Irawanti Irawanti; Rosida Rosida; Rosmini Rosmini; Nurul Sakina (Universitas Mataram, 2021)
Telaga Baru A is one of the area located in Telaga Bertong Village, Taliwang District, West Sumbawa Regency, West Nusa Tenggara Province, which had not used the house yard to improve the community's economy and national food security. One of the applicable steps that can be applied to optimize the yards of residents is the